Reducing Math Anxiety and Strengthening STEM Pathways: A Conceptual-Pedagogical Approach - Chowdhury, Pinaki (Universitas Negeri Semarang, 2025)
The development of skills among students in STEM fields is not only a pressing concern in countries like India and South Africa — it is a universal need. In an increasingly technology-driven world, building cognitive strength, attention capacity, and analytical reasoning from an early age has become a foundational requirement in education. While both India and South Africa have made progress in schooling, significant challenges remain, particularly in nurturing the critical thinking disposition among learners. This paper compares the two systems to observe visible gaps, especially in high school education, and examines how these gaps begin forming as early as childhood. The idea of learning through the body, particularly through the use of fingers, is explored with the support of Vedic mathematical techniques. A three-stage pedagogical approach is proposed, which not only introduces number concepts at an early age but also builds a bridge between the concrete and the abstract. This organic and tactile method reduces mathematics anxiety and fosters resilience. The Indian school system’s restriction on calculator use until Grade 12 is noted to preserve cognitive engagement, whereas early reliance on calculators in South Africa may unintentionally hinder analytical development. This paper ultimately suggests that using one’s own body as a natural learning tool not only improves numerical fluency but also cultivates a stronger critical thinking disposition, which is essential for solving the larger issue of STEM skill shortages in the future.